The mitochondrial genome of Toxocara canis. - Aaron R Jex; Andrea Waeschenbach; D Timothy J Littlewood; Min Hu; Robin B Gasser (Public Library of Science (PLoS), 2008)
Toxocara canis (Ascaridida: Nematoda), which parasitizes (at the adult stage) the small intestine of canids, can be transmitted to a range of other mammals, including humans, and can cause the disease toxocariasis. Despite its significance as a pathogen, the genetics, epidemiology and biology of this parasite remain poorly understood. In addition, the zoonotic potential of related species of Toxocara, such as T. cati and T. malaysiensis, is not well known. Mitochondrial DNA is known to provide genetic markers for investigations in these areas, but complete mitochondrial genomic data have been lacking for T. canis and its congeners. In the present study, the mitochondrial genome of T. canis was amplified by long-range polymerase chain reaction (long PCR) and sequenced using a primer-walking strategy. This circular mitochondrial genome was 14162 bp and contained 12 protein-coding, 22 transfer RNA, and 2 ribosomal RNA genes consistent for secementean nematodes, including Ascaris suum and Anisakis simplex (Ascaridida). The mitochondrial genome of T. canis provides genetic markers for studies into the systematics, population genetics and epidemiology of this zoonotic parasite and its congeners. Such markers can now be used in prospecting for cryptic species and for exploring host specificity and zoonotic potential, thus underpinning the prevention and control of toxocariasis in humans and other hosts.